The role of training and development on organisational performance in the footwear industry in South Africa - Ngcobo, Sanele Daniel (Technium Social Sciences Journal, 2022)
Training and development may not be a panacea for all the challenges that organisations face in the 21st century, but it has important implications on employee performance and overall organisational performance. Organisations that want to improve performance and productivity can do so through leveraging their most valuable resource, its people. The significance of this study is to inform curriculum developers about the skills shortage in the footwear industry in South Africa. The core problem this study seeks to address is the skills shortage in the footwear industry in South Africa. Furthermore, currently in KwaZulu-Natal, universities, technical and vocational education do not provide training on footwear. The mixed research method was employed. The purposive sampling was used to select the participants from Dick Whittington Shoes (Pty) Ltd Questionnaires, focus group interviews and document reviews were used to gather data. The findings of the study show that the human resource manager is facing a serious challenge from employees, which is a higher rate of absenteeism this hamper the performance of the organisation. The study found that the majority of employees are above the age of 55 years. In addition, they retire the organisation will re-employ them on the contract bases precisely because they find it hard to find incumbent with skills. The study recommended the need for a proper framework on continuous training and development of employees in the footwear industry in South Africa. Secondly, the public-private partnership with universities to bridge the skills gap and improve the gross domestic product in South Africa if implemented this could bring a resolution to the problems and challenges posed.